A fast approach for unsteady compressor performance simulation under boundary condition caused by pressure gain combustion. (September 2021) - Neumann, Nicolai; Asli, Majid; Garan, Niclas; Peitsch, Dieter; Stathopoulos, Panagiotis
Highlights: Introduction of a coupled numerical scheme of 0D-plenum and 1D-pulsed detonation combustion tubes. Compressor simulation with unsteady boundary condition caused by pressure gain combustion. Unsteady 1D-Euler results match those computed by unsteady 3D-CFD. 90% of the fluctuation's amplitude is damped across four stages of the compressor. Stability evaluation of a compressor exposed to pulsed detonation combustion. Abstract: The constant pressure combustion of the Joule cycle is a dominant source of losses in gas turbines. One possible improvement is pressure gain combustion through pulse detonation combustion. However, the total pressure increase is the result of a transient periodic process that can adversely affect the performance of adjoining turbo components. The thermodynamic benefits of pressure gain combustion can thus be undermined by low efficiencies of compressor and turbine. In order to account for such unsteady effects early in the design process, suitable methods are essential. Given 3D-CFD simulations' undue computational demands, an approach with low computation resources is required for first-order estimates. This paper introduces such an approach based on a 1D-Euler method and demonstrates its applicability. A compressor is simulated with 3D-CFD, which serves as a reference, as well as with the 1D-Euler code employing unsteady outlet boundary conditions that approximate those encountered with pulse detonation combustion. The findings suggest that the 1D-Euler code is able to accurately capture the transient compressor behaviour. Though the relative pressure amplitude at the compressor outlet of 3.6% is attenuated by 90% up to the compressor inlet, it still results in a compressor isentropic efficiency loss of 0.8 percentage points.